PREVALENCE OF DEPRESSION AND ANXIETY AMONG PATIENTS OF BRONCHIAL ASTHMA IN SOUTHERN RAJASTHAN - Dr. Manshi Borah; Dr. Shilpa Kakani; Dr. Abdul Sajid Mansoori (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
: Bronchial Asthma (BA) is a chronic respiratory condition that affects millions globally, with rising prevalence. Asthma has significant physical and psychological impacts, often leading to anxiety and depression among affected individuals. This study aims to assess the prevalence of depression and anxiety among patients diagnosed with BA and to explore potential correlations between these psychological conditions and asthma exacerbations.Methods: This cross-sectional, observational study was conducted at the Department of Pulmonology & Psychiatry, GBH Medical College and Hospital, Udaipur. A total of 50 diagnosed asthmatic patients aged between 20 and 60 years were included. Anxiety and depression were assessed using the Hospital Anxiety and Depression Scale (HADS), with scores categorized as mild, moderate, or severe. The study also explored correlations with gender, area of residence, and educational status.Results: Out of the 50 asthmatic patients, 28% exhibited anxiety, and 24% exhibited depression. The prevalence of mild anxiety (95%) and mild depression (97%) was the highest among the patients. Anxiety was more prevalent among females (40%) than males (14%), while depression was more common in males (12%) than females (8%). Patients from rural areas and those with lower educational status exhibited higher rates of both anxiety and depression. Statistically significant associations were found between anxiety and depression with the area of residence (P = 0.001) and educational status (P = 0.001). Conclusion: The study highlights a significant prevalence of anxiety and depression among asthmatic patients. Factors such as gender, area of residence, and educational level were identified as key variables influencing the mental health status of asthma patients. Addressing these psychological comorbidities may improve overall disease management and enhance the quality of life for asthma patients.